Polar Movement of Indole-3-acetic Acid-(14)C in Roots of Lens and Phaseolus - Kirk, Susan C. (1968)
A critical review of the few papers on IAA-(14)C movement in roots revealed apparent contradictions, as well as flaws in experimental design that would be apt to cause artifacts. The movement of (14)C from IAA-(14)C was studied in sections of Lens and Phaseolus roots, using a system 20 or more times as sensitive as any previously used. To make sure that our results with roots could be compared validly with published work on petioles and stems, we used the same techniques as we had earlier used for shoot structures. The results with Lens were similar in many ways to those for shoots: net movement into receiver blocks was very strongly polar, followed a linear course for several hours, and showed a velocity of the same order of magnitude as in shoots (and, in fact, very close in absolute value to that found in Coleus stem cylinders). Also, as with shoots, all the radioactivity in receiver blocks ran to the R(F) of IAA. The time-course of loss of counts from donor blocks was similar to that found in shoots. The 2 most striking differences from shoots were 1) the very low percentage of added (14)C that was moved into the receivers (about one-tenth of the values for bean petioles), and 2) the fact that the polar movement was acropetal in roots, rather than basipetal as in shoots. Results with Phaseolus roots were similar to those for Lens, although an additional complication with Phaseolus roots was the indication of a transitory stage of weak basipetal polarity in the first few hours after excising the section. This stage was followed in a few hours by a stronger acropetal polarity.